Contribution of Students' Learning Motivation and Numerical Ability to The Learning Outcomes of Chemistry Calculations During the Pandemic. - Rastuti, Sri (Science Education and Application Journal, 2023)
The purpose of this study was to determine and analyze the contribution of students' learning motivation and numerical ability to the learning outcomes of chemistry count material. This research is quantitative research. The research method was carried out utilizing sampling technique using a proportional classical random sampling technique. Data was collected using multiple-choice tests and Likert scale model questionnaires. Respondents in this study were students of class Ten Science Senior Hight School One Karangdowo total 90 student. Analysis of the data used is a technique of partial correlation analysis and linear regression of two predictors. The results of this study indicate that: there is a significant positive contribution between learning motivation and numerical ability together to the learning outcomes of chemistry in the matter of chemistry. Partially, it shows that there is no significant positive contribution between learning motivation and learning outcomes for the matter of chemistry. Partially, it shows that there is a significant positive contribution between numerical ability on learning outcomes of chemistry calculations. The effective contribution of learning motivation is 0.65% and numerical ability is 8.47%. This shows that during a pandemic, learning motivation contributes less than numerical abilities.